2007
DOI: 10.3149/fth.0503.197
|View full text |Cite
|
Sign up to set email alerts
|

Parenting Predictors of Father-Child Attachment Security: Interactive Effects of Father Involvement and Fathering Quality

Abstract: This study examined the parenting predictors of father-child attachment security in early childhood. Results suggest that multiple dimensions of fathers' parenting quality moderated the associations between father involvement, in its original content-free sense, and father-child attachment. Specifically, father involvement was generally unrelated to attachment security when fathers engaged in high-quality parenting behavior, but associated with lower levels of attachment security when fathers' parenting was le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
67
2
7

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 68 publications
2
67
2
7
Order By: Relevance
“…In other studies either no associations were found or (negative) interactive effects have been reported (e.g., Brown et al, 2007;Cox et al, 1992;Easterbrooks & Goldberg, 1984). Even so, in this sample fathers who shared child-care tasks to a greater extent had children with higher AQS security scores.…”
Section: Discussioncontrasting
confidence: 41%
See 2 more Smart Citations
“…In other studies either no associations were found or (negative) interactive effects have been reported (e.g., Brown et al, 2007;Cox et al, 1992;Easterbrooks & Goldberg, 1984). Even so, in this sample fathers who shared child-care tasks to a greater extent had children with higher AQS security scores.…”
Section: Discussioncontrasting
confidence: 41%
“…Easterbrooks and Goldberg (1984) reported that father involvement (quantity of time spent with the child) contributed uniquely to child development, independent of associations with the quality of parenting behaviours (although quality also explained a significant proportion of outcome variance), but parent involvement and parenting characteristics simultaneously accounted for a larger proportion of the outcome variance, than either set of characteristics alone. Brown et al (2007) reported that fathers' parenting quality and involvement (i.e., quantity) had interactive effects on child-father attachment relationship. For fathers exhibiting positive parenting behaviours, their degree of engagement did not significantly predict attachment security.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…If parents aren't sensible and responsive to child clues, even play activities (usually seen as enjoyable, reciprocal and pleasurable) can be a context for demanding, intrusive or hostile interactions (Brown et al, 2007). In this study, parenting styles were used as "quality" indicator.…”
Section: Discussionmentioning
confidence: 99%
“…Although initial studies have focused mainly on the presence/absence of fathers and how much time they spent with their children, while this data is fundamental, it is critical to also capture the quality of these interactions and involvement (Brown, McBride, Shin, & Bost, 2007;Coyl-Shepherd, & Newland, 2013;Tremblay & Pierce, 2011). Father involvement should, therefore, be understood as a complex and multidimensional construct, that comprises behaviors, emotions and cognitions (Hawkins & Palkovitz, 1999), and different contexts of interaction (e.g., care or play) (Parke, 1996).…”
mentioning
confidence: 99%